2020
DOI: 10.3390/f11121284
|View full text |Cite
|
Sign up to set email alerts
|

Studies into Fungal Decay of Wood In Ground Contact—Part 1: The Influence of Water-Holding Capacity, Moisture Content, and Temperature of Soil Substrates on Fungal Decay of Selected Timbers

Abstract: This article presents the results from two separate studies investigating the decay of wood in ground contact using adapted versions of laboratory-based terrestrial microcosm (TMC) tests according to CEN/TS 15083-2:2005. The first study (A) sought to isolate the effect of soil water-holding capacity (WHCsoil [%]) and soil moisture content (MCsoil [%WHCsoil]) on the decay of five commercially important wood species; European beech (Fagus sylvatica), English oak heartwood (Quercus robur), Norway spruce (Picea ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…(2) Precipitation-sensitivity: Microbial activity and substrate access are dependent on moisture [37][38][39][40] . We predicted microbial decomposition will be highest in humid locations.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Precipitation-sensitivity: Microbial activity and substrate access are dependent on moisture [37][38][39][40] . We predicted microbial decomposition will be highest in humid locations.…”
Section: Main Textmentioning
confidence: 99%
“…These results suggest that while precipitation shapes the discovery phase, it does not affect the decay phase of termite decomposition; however, the strong temperature and precipitation interaction effect on discovery means that termites increase overall decay most in tropical seasonal forests and savannas and subtropical deserts (Figure 1C). Further, even though microbial abundance is highly sensitive to precipitation [37][38][39][40] , temperature was a stronger driver than precipitation of microbial-driven decay, perhaps mediated through its effects on enzyme kinetics 36 .…”
Section: Main Textmentioning
confidence: 99%
“…The progress of decay in-ground is less affected by the wetting ability of wood, since wood mainly stays permanently wet when it is exposed to soil [86][87][88]. Wood that has undergone non-biocidal treatments, aimed at the exclusion of moisture from the cell walls, are therefore often not recommended for use in soil contact where intermediate re-drying is not possible.…”
Section: Modelling Materials Resistance In Soil Contactmentioning
confidence: 99%
“…It has been found that the presence of brown rot fungi changes the penetration of liquid water into a piece of wood (Frankl 2013 ). Some papers present results on the observation of the decay of wood buried in the ground (Marais et al 2020 ), fungal decay resistance by coating (De Vetter et al 2009 ), the effects of soil and wood water content on fungal decay (Brischke and Alfredsen 2020 ), and the aging of the coating and cracking of the surface increasing the permeability of the wood (Ekstedt 2003 ).…”
Section: Introductionmentioning
confidence: 99%